Can role models increase young women’s interest in IT training occupations? : “VET ambassadors” as an example of career orientation based on social approval - Beckmann, Janina [Verfasser]; Esteve, Alba Estela [Verfasser]; Granato, Mona [Verfasser] (My University, 2023)
"In view of the shortage of skilled workers and a pronounced underrepresentation of women in IT professions in Germany, this study asks whether vocational role models can attract more young people, especially more young women, to IT professions. This study uses the example of “VET ambassadors” in Germany – a novel career orientation approach based on social identification and social approval – to study the impact of vocational role models on students’ career preferences. Initial results from the BIBB-TUDa-Career Orientation Study suggest that role models may reduce gender differences in students’ occupational knowledge, self-efficacy and career preferences for IT professions." (authors' abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; S 6.4.9 IT-Berufe; L 5 Beratung & Orientierung; G 2.4.5 Gender Mainstreaming; 370; Weibliche Jugendliche; Junger Erwachsener; IT-Beruf; Fachinformatiker; Berufsorientierung; Geschlechterrolle; Geschlechtersegregation; Vorbild